The Effectiveness of Archived E-Book Based Curriculum 2013 as an Effort to Improving Learning Outcomes in Vocational School - Chairul Huda Atma Dirgatama; Siswandari Siswandari; C. Dyah Sulistyaningrum Indrawati (Journal of Education and Learning (EduLearn), 2017)
In digital era, the role of media as a helping tool in the process of teaching learning is very important. It is also the right choice in improving the quality of education. The purpose of this research is to find out whether archived e-book based curriculum 2013 which has been developed is effective to improve the learning outcomes in Vocational School. This was a research and development study. The data for the media developed used Sigil software with the help of Supreader software. The instrument was validated by experts. The instrument used in this study was a questionnaire and tests. Interviews and observations were analyzed with descriptive qualitative, whereas the questionnaire and test were analyzed by descriptive quantitative tests. This study used SPSS 20 and IBM software to calculate the data. Based on the analysis, the mean score of experimental group was 81.25 and the control group was 75.94 for their post-test. The t-test score for t-observed was 2.53 meanwhile the t-table was 2.00. The null hypothesis was rejected because t-observes was higher than t-table. It implied that the experimental group performed better than the control group. The conclusion was that learning media using archived e-book based curriculum 2013 was effective to improve learning outcomes. It was based on the t-test calculation in the significant error of 0.05. So there was a significant difference between the mean score of experimental and control group.